Letter: can addition of an immunomodulator really reverse antibody formation and loss of response in patients treated with adalimumab? Authors' reply. Issue 5 (2nd February 2017) - Ben‐Horin, S.; Ungar, B.; Roblin, X.
Abstract : Linked Content This article is linked to Ungar et al and Bendtzen and Steenholdt papers. To view these articles visithttps://doi.org/10.1111/apt.13862 andhttps://doi.org/10.1111/apt.13921 .